Field cancerization in women without conventional risk factors: insights from a case-cohort study - Martina Coppini; Martina Coppini; Giuseppe Seminara; Giuseppe Seminara; Rodolfo Mauceri; Rodolfo Mauceri; Olga Di Fede; Gaetano La Mantia; Gaetano La Mantia; Nicola Mauceri; Valeria Cancila; Vito Rodolico; et al. (Frontiers in Oral Health)
BackgroundField cancerization (FC) is a well-documented phenomenon in oral squamous cell carcinoma (OSCC), typically reported in patients with known risk habits such as tobacco and alcohol use. To date, limited evidence exists regarding FC in individuals without traditional carcinogenic exposures, as well as in those associated with chronic mechanical trauma. The study aims to report a case series of FC in patients without well-known risk habits observed in the last two years.Material and methodsThis study is a retrospective cohort study conducted at the Unit of Oral Medicine “V. Margiotta” of the University Hospital “Paolo Giaccone” in Palermo (Italy). Between January 2023 and February 2025, a total of 64 patients affected by OSCC were observed. All cases were histologically confirmed through biopsy. For the present study, we focused specifically on the subgroup of patients who developed synchronous and/or metachronous lesions during this period.ResultsA retrospective analysis was conducted on eight female patients (mean age: 75.5 ± 10.3 years) diagnosed with multifocal OSCC. Three patients presented with synchronous lesions, three with metachronous lesions, and two developed both types over time. Six patients (75%) were denture wearers.ConclusionsThis study highlights the relevance of FC in elderly OSCC patients with no history of traditional carcinogenic exposures, except for the high prevalence of denture use, which, however, cannot be considered a clear causal factor. Long-term clinical and radiological surveillance is essential for early detection of multifocal lesions, thereby improving prognosis and patient quality of life.